The exegetical encounter between Jews and Christians in late antiquity - Grypeou, Emmanouela; Spurling, Helen (Jewish and Christian perspectives series, 2009)
Adam alone in Paradise : a Jewish-Christian exegesis and its implications for the history of asceticism / Dmitrij F. Bumazhov -- Will and grace : apsects of judaising in Pelagianism in light of Rabbinic and patristic exegesis of Genesis / Burton L. Visotzky -- The Christian and the rabbinic Adam : Genesis Rabbah and patristic exegesis of Gen 3:17-19 / Hanneke Reuling -- Critical gnostic interpretations of Genesis / Gerard P. Luttikhuizen -- 'Be you a lyre for me' : identity and manipulation in Eden / Michael E. Stone -- What did Cain do wrong? : Jewish and Christian exegesis of Genesis 4:3-6 / Robert Hayward -- Creating women's voices : Sarah and Tamar in some Syriac narrative poems / Sebastian P. Brock -- Genesis 15 in rabbinic and patristic interpretation / Günter Stemberger -- 'And Abraham had faith,' but in what? : Ephrem and the rabbis on Abraham and God's blessings / Judith Frishman -- Abraham's angels : Jewish and Christian exegesis of Genesis 18-19 / Emmanouela Grypeou, Helen Spurling -- Keeping it in the family : Jacob and his Aramean heritage according to Jewish and Christian sources / Alison Salvesen -- Early rabbinic exegesis of Genesis 38 / Stefan C. Reif -- Origen's view of 'Jewish fables' in Genesis / Marc Hirshman